CAREER OF GRADUATES HADITH SCIENCE STUDY PROGRAMME ACCORDING TO THE SANTRI: A STUDY OF SANTRI PERCEPTIONS IN KEDIRI ISLAMIC BOARDING SCHOOL - Khoir, Moh. Misbakhul; Hariono, Duwi; Barti, Ananda Ivano; Yunus, Muhammad (Jurnal Studi Hadis Nusantara, 2025)
The Hadith Science Study Programme is a unique study programme when compared to other study programmes. One of the factors contributing to this is the assumption that the career prospects of graduates from the Hadith Science Study Programme are limited and less financially promising. In this context, santri, as a group that has an affinity with Islamic studies, is an important subject to explore their perceptions. Their understanding of the career opportunities of graduates of the Hadith Science Study Programme can provide an overview of the factors that influence interest in this study and how the development strategy is going forward. This study aims to reveal the santri's perceptions of the career prospects of graduates of the Hadith Science Study Programme. This study was conducted in three Islamic boarding schools in Kediri, namely Pondok Pesantren Al-Mahrusiyah Lirboyo Kediri, Al-Islah Bandar Kidul Kediri and Raudlatul Ulum Kencong Kediri, using a phenomenological qualitative approach. Data were collected through observation, semi-structured interviews, and documentation. It was then analysed using the Miles and Huberman qualitative analysis model. The results showed that santri have diverse views on the career prospects of Hadith Science graduates. Most santri consider that careers in this field are more limited compared to general study programmes. Although professions such as Hadith teachers and preachers are considered noble, financial challenges are the main obstacle. However, the digital era opens up new opportunities for graduates of the Hadith Studies Program, such as becoming religious content creators and developing Hadith digitisation tools. Therefore, the development of academic strategies and career support for graduates of the Hadith Science Study Programme is important. Universities also need to innovate in learning and socialisation of the Hadith Science Study Program to make it more attractive and relevant to the needs of the current world of work.